Kemampuan Komunikasi Matematik Siswa Berdasarkan Gender: Suatu Kasus di Sekolah Berbasis Pesantren - Dahiana, Wa Ode; Herman, Tatang (Universitas PGRI Madiun, 2021)
The purpose of this study was to determine differences in students' mathematical communication skills based on gender with learning using metacognitive strategies. This research method is a quasi-experimental design using a pretest-posttest control group design. The sampling technique used was saturated sampling which consisted of 19 male students as the first experimental group and 17 female students as the second experimental group. The instrument used was in the form of a five-point essay test to measure the aspects of students' mathematical communication skills after being given a treatment, namely learning using metacognitive strategies. The pre-test mean score shows that female students are higher than male students, on the contrary, the average score of the post-test results, it is known that male students are higher. The data were analyzed using the t-test, it was concluded that there was a significant difference between the mathematical abilities of male and female students. This difference is consistent with several previous research results, although not a few studies also state that there is no significant difference between students' academic abilities based on gender.